IDENTIFIKASI KOMPONEN KIMIA DAN FITOKIMIA DURIAN LAHUNG (Durio dulcis) INDIGENOUS KALIMANTAN - Susi Susi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
South Kalimantan was one of the areas rich in biological resources, including indigenous fruits. Indigenous and exotic fruits have not been widely known and most have not been used optimally. Indonesia is one of the eight centers of plant genetic diversity in the world, especially to tropical fruits such as durian (Durio spp.), and Kalimantan is an important distribution center for various types of durian, one of them was Lahung (Durio dulcis). Lahung had the sweetest taste among others, but their use is still limited. Based on its chemical characteristics of Lahung showed potential for development as refined products in order to develop agroindustry and also for the development of functional food sources that are beneficial to health. Preliminary analysis conducted on nutrition of fruit, including analysis of water content, fat, protein, ash, fiber, carbohydrates, total acid, and vitamin C, fatty acid composition, amino acid composition and qualitative test of phytochemicals in the fruit flesh and seeds. Test results showed lahung flesh significant containing fat and protein, whereas the seeds containing dominan amino acid sand crude fiber. Essential fatty acids in the flesh of the fruit were glinoleic, linolenic, EPA and DHA, while essential amino acids in the fruit flesh was tyrosine, and valine in the fruit seeds. The fruit flesh and seeds contain alkaloids. Keywords : Durio dulcis, fatty acid, amino acid, phytochemical